Casebook of neuropsychiatry - Hurwitz, Trevor A., 1950-; Lee, Warren T., 1963-; American Psychiatric Association (Washington, DC : American Psychiatric Pub., 2013)
Comprised of 38 clinical cases based on real patient interactions that straddle the domains of neurology and psychiatry. While scientifically rigorous and grounded in neuroanatomy and neurochemistry, the cases are written in an accessible, down-to-earth style that makes them easy to relate to and understand. The book is designed to supplement comprehensive texts (such as Yudofsky's "American Psychiatric Publishing Textbook of Neuropsychiatry and Behavioral Neuroscience, Fifth Edition") by providing real-world accounts of patient presentations - such as dopamine excess in a Parkinson's patient or post-stroke depression that clinicians are likely to encounter. The book focuses on skills that are not typically emphasized in general psychiatric or neurological training, filling a critical gap and broadening the reader's knowledge base. The book takes the clinical presentation as the starting point, using a specific case to describe the approach, the differential diagnosis, the diagnostic workup, the neuroanatomical and neurochemical basis of psychopathology, and contemporary treatment options
Psychobehavioral disinhibition -- Apathy -- Depression -- Anxiety -- Psychosis -- Hyperkinetic states -- Somatoform and somatoform-like disorders -- Alterations in consciousness -- Memory failure -- Intellectual failure -- Focal neurobehavioral syndromes.
Includes bibliographical references and index.
Print version record.
WorldCat record variable field(s) change: 650
Keywords: Psychiatry -- Case studies; Mental illness; Mental Disorders; Neurobehavioral Manifestations; Neuropsychiatry -- methods